MUGHAL CARPET COLOR MAKING PROCESS (WITH REFERENCE TO THE JAHANGIR ERA): मुगल कालीन रंग निर्माण -प्रक्रिया (जहाँगीर काल के संदर्भ में) - Dhiman, Rekha (International Journal of Research -GRANTHAALAYAH, 2014)
Mughal painting maintains an independent and significant identity throughout Asia. Babur, the fifth generation of Timur Vansh, established Mughal culture in 1527 by dominating some parts of India. Which was extended by the rulers of Humayun, Akbar, Jahangir, Shahjahan and Aurangzeb. At this time, all the arts developed properly. Mughal carpet painting was at its peak till the reign of Shahjahan. Iranian, Chinese and Western art styles influenced this. At this time the painting was effective as miniature and crystal painting. ’Jahangir period (from 1605 to 1627 AD) painting was in its youth in the form of miniatures. Senior painters in the schools of paintings used to study the subjects practically as well as impart an important chapter in the ’Rangamiji in miniatures’ according to Nassab Talim. This was the reason that Jahangiric painting was achieved to the extreme. Provided the method of color mixing to Lipi. 2 Under this, special attention was given to color formation process and color composition. Senior painters used to train the subjects to collect natural, mineral and chemical tissue stems under their own supervision. During the Jahangir period, color manufacturing was done in India itself and exported to other countries. Therefore, special attention was also paid to color making method. म्ुागल चित्रकला सम्पूर्ण एषिया में स्वतंत्र और महत्वपूर्ण पहचान बनाये हुए है। तैमूर वंष की पांचवी पीढ़ी के बाबर ने सन् 1527 में भारत के कुछ हिस्सों पर अपना आधिपत्य कर मुगल संस्कृति को स्थापित किया। जिसे हुमांयू , अकबर, जहाँगीर, षाहजहँा और औरंगजेब आदि षासकों ने विस्तार दिया। इस समय सभी कलाओं का समुचित विकास हुआ। षाहजहँा के षासन काल तक म्ुागल कालीन चित्रकला चरम - वैभव को प्राप्त थी। इस पर ईरानी, चीनी और पष्चिमी कला षैली का प्रभाव पडा। इस समय चित्रकला लघु और स्फुट चित्रों के रुप प्रभावषाली रही। ’जहाँगीर काल (1605 से 1627 ई. तक) चित्रकला लघुचित्रों के रुप में अपने यौवन पर थी।‘1 जहाँगीर ने अपने षासनकाल में चित्रषालाओं की स्थापना की और चित्रकारों को संरक्षण प्रदान किया। चित्रषालाओं में वरिष्ठ चित्रकार षिष्यों को व्यवहारिक रुप से अध्ययन कराते थे ही साथ ही नसाब तालीम अनुसार ’ लघुचित्रों में रंगामेजी ’ महत्वपूर्ण अध्याय की तालीम दिया करते् थे।यही कारण था कि जहाॅंगीरकालीन चित्रकला चरमसीमा को पाप्त हुई।’मरवादीद ने सम्पूर्ण मुगलों की चित्रकला अैर लिपी को रंग मिश्रण का विधान सुलभ कराया। 2 इसके अंतर्गत रंग निर्माण प्रक्रिया और रंग संयोजन को विषेष महत्व दिया जाता था। वरिष्ठ चित्रकार षिष्यों को स्वयं के निरीक्षणमें प्राकृतिक, खनिज और रासायनिक तंू उंजमतपंस एकत्रित करने का प्रषिक्षण देते थे। जहाँगीर काल में रंग निर्माण का कार्य भारत में ही होता था और अन्य देषों को निर्यात किया जाता था। अतः रंग निर्माण पद्यति पर भी विषेष ध्यान दिया जाता था।